Kinetic Study of Color, Texture and Exergy Analysis of Halloumi Cheese During Deep-Fat Frying Process - Erim Kose, Yagmur (MDPI, 2025)
Halloumi cheese is commonly consumed in fried form, yet the effects of frying conditions on its quality and energy performance have not been fully clarified. This study aimed to investigate the color and texture changes of halloumi cheese during deep-fat frying at 140, 150 and 160 degrees C for 0, 2, 4, 6 and 8 min. It also evaluated the exergy efficiency of the process to clarify how frying temperature and time influence energy use. Based on regression analysis, the reaction kinetics of L*, a*, and b* followed first-order behavior, while changes in Delta E were best described by a zero-order model. The texture parameters chewiness and springiness decreased in accordance with first-order kinetics, whereas the observed increases in hardness and adhesiveness followed a zero-order reaction model. Activation energies for both color and texture changes, calculated using the Arrhenius equation, ranged from 12.976 to 50.857 kJ/mol. Exergy efficiency varied between 31.08% and 46.83%, with the highest value obtained at 150 degrees C for 8 min. The combined kinetic and exergy approach provides practical information for selecting frying conditions that ensure consistent quality while improving energy use in fried dairy products.
Keywords: activation energy; color kinetic; exergy analysis; halloumi cheese; kinetic modeling; texture kinetic; FOOD; QUALITY; HEAT; MILK; ENERGY; OVINE; Engineering